ORGANIZATION OF PROSPECTIVE TEACHER-MUSICIAN'S CREATIVE COMPETENCE: THE REFLEXIVE ASPECT - Tatyana A. Kolisheva; Irina A. Petsina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article reviewed the problem of formation of the creative competency of future music teachers and the results of putting their knowledge and creative experience based on professional self-reflection to use. Professional self-reflection of a music teacher conduces deep understanding of the meaning of creativeness in his profession; internal self-enrichment and self-actualization; allows to developing a program of demands on themselves, the process and the results of creative activity; contributes to a sequence of generalized professional experience and skills. Proved that the formation of professional and self-reflection of music teachers assist the use of dialogue and democratic style of dialogue, free exchange of ideas, creative discussion, which summarized the ideas of solving the problem (interpretation of creative problem to a successful solution). Particular attention is paid to the organization and training of game forms of teaching which aimed at development of reflective thinking, creative communication, artistic and technological skills.